Simulations of electromagnetic transients in a transmission line using state variables - Canonico, R. B. (2008)
Transmission lines can be represented by a set of pi circuits. These circuits can be modeled by state variables and solved using trapezoidal integration. This paper presents a mathematical routine that, using trapezoidal integration techniques, is adequate to simulate the wave propagation on the transmission lines based on state variables. The presented routine is not complicate and has satisfactory accuracy for initial analyses about wave propagation by training students. So, several input signal types are simulated using a mathematical routine that is not complicate and is suitable for the first contact with wave propagation phenomena. The model presented in this article is simple, adequate for students who are beginning the analysis of transient phenomena in power systems. A basic model of a transmission line is proposed, which can be introduced on a matrix calculation program, creating the possibility of electromagnetic transient simulations. The objective is to make possible the manipulation of the mathematical model by undergraduate students interested in the study of transmission lines.